Afro-Americans Struggle for Political Equality The Rise of Barak Obama - Hinnichi, Khaled; Gatcha ,Bouzid Yacine; Aribi, Ibrahim (Faculty of Letters and Foreign Languages Department of English, 2016)
The case of Africans is a very delicate issue in the history of America, it plays a crucial part in shaping the US history, as Afro-Americans struggled and suffered many years from slavery till they gain their freedom. The present work represents an attempt to discuss the development of the African Americans through different stages; our main focus in this paper is the political leaders in the African history and how they contributed in leading their people